Investigation of the intensity of strain hardening of low‑carbon steel. - V. P. Fetisov (Литьë и металлургия, 2025)
The influence of the deformation scheme under uniform and concentrated tension, compression and drawing on the intensity of strain hardening of low‑carbon steel with different dispersion of the structure is considered. With an increase in the grain size of ferrite, the tendency to hardening increases for all deformation schemes. Compression reduces the structural sensitivity of the intensity of strain hardening. Uniform tension enhances the intensity of hardening compared to drawing and concentrated tension, but is inferior to uniaxial compression. The breakthrough of dislocation accumulations through the subsurface layers of the wire of the stronger surface layer formed during drawing is accompanied by an increase in the density of mobile dislocations and a decrease in the intensity of strain hardening.